2021
DOI: 10.2478/jlecol-2021-0008
|View full text |Cite
|
Sign up to set email alerts
|

Public Perception of Biodiversity: A Literature Review of Its Role in Urban Green Spaces

Abstract: The significance of biodiversity in the survival of human beings and enhancing the urban quality of life is evident from the empirical measurements and qualitative studies carried out across the globe. Despite its importance and value, burgeoning population and growing urbanization are posing a serious threat to biodiversity leading to biodiversity homogenization and ecosystem fragmentation. Moreover, studies reveal that management practices of biodiversity hardly take into account perception, needs, and knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…Studies from a range of countries on the perception of UGSs have identified several dominant factors that influence public perceptions (Tian et al, 2020). Bele and Chakradeo (2021) suggest that socio-economic aspects such as gender, age, religion, and marital status should be included in the determination of perceptions of urban green spaces. Gashu et al (2020), in their study in Ethiopia, argue that demographic, socio-economic, institutional, and physical factors contribute to different perceptions of green infrastructure.…”
Section: Socio-demographic and Economic Factors Influencing The Perceptions Of Ugssmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies from a range of countries on the perception of UGSs have identified several dominant factors that influence public perceptions (Tian et al, 2020). Bele and Chakradeo (2021) suggest that socio-economic aspects such as gender, age, religion, and marital status should be included in the determination of perceptions of urban green spaces. Gashu et al (2020), in their study in Ethiopia, argue that demographic, socio-economic, institutional, and physical factors contribute to different perceptions of green infrastructure.…”
Section: Socio-demographic and Economic Factors Influencing The Perceptions Of Ugssmentioning
confidence: 99%
“…Mathey et al (2018) observed that brownfields in urban areas with natural vegetation cover could positively contribute to the biodiversity of urban green systems. In their literature review of the public perception of biodiversity in UGSs, Bele and Chakradeo (2021) emphasize the significance and value of biodiversity on the quality of life in urban areas. They argue that despite the crucial role that urban green spaces play in maintaining urban biodiversity, the association of biodiversity, urban green spaces, and public perception had not received sufficient attention.…”
Section: Ugss and Biodiversitymentioning
confidence: 99%
See 3 more Smart Citations